Thoraco-omphalopagus conjoined twin: a rare case report - Jain, Reema; Makhija, Nishi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Conjoined twins also known as Siamese twins, is a rarely seen congenital anomaly with an incidence as low as 1 in 50000 to 1 in 100 000 live births. Among various types of conjoined twin, commonest type is the thoracopagus type, where the fusion is anterior, at the chest, and involves the heart. There is a high rate of stillbirth and neonatal deaths resulting in very few cases surviving long enough for surgical separation. case report. We reported one case of multi gravid woman, admitted to our hospital with an ultrasound report of conjoined thoracopagus twin at 19 weeks gestation. Surgical termination of pregnancy was done. Conclusion. Making an early diagnosis with ultrasonographic examination gives the parents a chance to elect pregnancy termination and avoid life threatening neonatal complications.